Por obligación de conciencia. Los misioneros del Carmen Descalzo en Urabá (Colombia), 1918-1941 (2007)
ABSTRACT: The misional project of Carmelite the barefoot ones, like many others of the time, reinforced its legitimation resorting to the socialization of the penalties undergone in the misional jurisdiction. A language shared by the powers public, the citizenship and the monks consolidated therefore whom the moral judgment of the region of Urabá implied, thought from long ago like a dense and dangerous forest, bordered by a sea enraged and sunk in the barbarism, that demanded the redentora work of the mission.